Strategies to improve the therapeutic efficacy of mesenchymal stem cell‐derived extracellular vesicle (MSC-EV): a promising cell-free therapy for liver disease - Zheng, Lijuan; Gong, Hui; Zhang, Jing; Guo, Linna; Zhai, Zhuofan; Xia, Shuang; Hu, Zhiyu; Chang, Jing; Jiang, Yizhu; Huang, Xinran; Ge, Jingyi; Zhang, Bikui; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Liver disease has emerged as a significant worldwide health challenge due to its diverse causative factors and therapeutic complexities. The majority of liver diseases ultimately progress to end-stage liver disease and liver transplantation remains the only effective therapy with the limitations of donor organ shortage, lifelong immunosuppressants and expensive treatment costs. Numerous pre-clinical studies have revealed that extracellular vesicles released by mesenchymal stem cells (MSC-EV) exhibited considerable potential in treating liver diseases.Although natural MSC-EV has many potential advantages, some characteristics of MSC-EV, such as heterogeneity, uneven therapeutic effect, and rapid clearance in vivo constrain its clinical translation. In recent years, researchers have explored plenty of ways to improve the therapeutic efficacy and rotation rate of MSC-EV in the treatment of liver disease. In this review, we summarized current strategies to enhance the therapeutic potency of MSC-EV, mainly including optimization culture conditions in MSC or modifications of MSC-EV, aiming to facilitate the development and clinical application of MSC-EV in treating liver disease.